Efficiency of Coal Dust Suppression by Surfactants in Underground Mines: Investigation of the Role of Various Factors - Chen, Yinping (Curtin University, 2019)
During the 2.5-year full time and 2.5-year part time PhD study, I studied the impacts of various factors on coal dust suppression efficiency in presence of surfactants by using experimental methods and numerical simulation. The optimum method in terms of evaluating surfactants was determined by comparing all the static and dynamic methods. The optimum surfactant type and concentration range were recommended for coal dust concentration reduction.